Arbeit and Transformations in Workplace Structures: Three Post-Reunification German Novels - Syamsu Rijal (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2020)
Arbeit, as one of the themes of culture is considered relevant and representative in the study of foreign literatures. Three german novels that were written in the second decade after reunification (2000–2010) and that have Arbeit as their main theme were selected as the material object of this research: Das Jahr der Wunder by Reiner Merkel (2001), Wir schlafen nicht by Kathrin Röggla (2004), and Mobbing by Annette Pehnt (2007). This research's main goal is to obtain a greater understanding of Arbeit as presented in these three novels, and to see how authors have responded to dynamic developments within the workplace in Germany, particularly since reunification. This study utilized a perspective of sociology of literature by summarizing various theories that mainly related to the conception Arbeit to become a major foothold in elucidating various aspects based on the objectives of this study.This research shows that, Normal workplace relations have slowly shifted to anomalous workplace relations, and as a result workers have lost an ever increasing number of rights. Workers have been consciously exploited within the workplace, and the social inequalities within the workforce have challenged not only workers' dignity, but also their very existence. As such, the three writers discussed here have promoted a more humanized Arbeit—one which recognizes human dignity as central to its conceptual framework—for modern society.